Scientific publication from public and private's - Salzano, Sonia Della Torre; Stefanelli, Maguida Costa; Adami, Nilce Piva; Jorge, Ana Lúcia Silva; Castro, Rosa Aparecida Pimenta de; Silva, Isília Aparecida (Revista da Escola de Enfermagem da USP, 1998)
This study shows the nurse's scientific publication from seven public and six private hospitals in São Paulo city, from january/1989 to june/1995. From a total of 486 papers identified, 242 were published as abstracts, 124 in annals, 92 in nationals and internationals journals, 21 as book chapters and 7 as books in nursing. The facilities and difficulties in publishing nursing scientific production were also discussed.